KEPEMIMPINAN KEPALA SEKOLAH DALAM MENERAPKAN KONSEP MERDEKA BELAJAR - Nuryoso; Dwi Saputra; Muhammad M. Qawim; Ahmad Hariyadi; Slamet Utomo (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2023)
This conceptual article aims to examine the leadership of school principals in applying the concept of independent learning. The results of the study show that the principal's leadership has a central role in the implementation of independent learning in schools. The steps taken by the principal started from: implementing policies that support independent learning, encouraging teachers to implement fun learning, motivating students to have readiness and mood to learn, actively involving parents and the environment, and collaborating with the education office to holding training to improve teacher competence. Success in implementing independent learning by the principal is proven by the participation of students in education that is evenly distributed, the implementation of effective learning, and no students are left behind in the learning process.